2004
DOI: 10.1097/00003727-200410000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Mentoring Partnership Model

Abstract: The purpose of this project was to increase the number of students participating in public health nursing experiences at Vermont Department of Health through creation of a mentoring partnership model. The model targeted preceptor needs, including roles and responsibilities when working with students; educational needs of faculty, particularly related to evolving roles of public health nurses; and creation of additional clinical opportunities for students. Outcomes included improved working relationships among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This type of partnership allows academic and clinical services, utilizing evidence-based practice in care paradigms, will allow both institutions to foresee problems and be able to identify and evaluate them (Frank, 2008). Technological advancements have increased anxiety in the profession since they may require innovative interventions that have not been taught in schools and healthcare institutions (Sowan et al, 2004). However, working collaboratively provides a strategic approach that can accelerate adaptation and response to technology.…”
Section: Valuing Partnershipsmentioning
confidence: 99%
“…This type of partnership allows academic and clinical services, utilizing evidence-based practice in care paradigms, will allow both institutions to foresee problems and be able to identify and evaluate them (Frank, 2008). Technological advancements have increased anxiety in the profession since they may require innovative interventions that have not been taught in schools and healthcare institutions (Sowan et al, 2004). However, working collaboratively provides a strategic approach that can accelerate adaptation and response to technology.…”
Section: Valuing Partnershipsmentioning
confidence: 99%
“…Indeed, one of the strengths of the international practice-education partnerships is the defined role that nurse lecturers play in meeting the aims of the partnership. Roles performed include support and preparation for the preceptor (Haas et al 2002, Sowan et al 2004) and the development of specific student related activities (Hall-Long 2004). Chapple & Aston (2004) report on role flexibility, with the role activities performed by the multiple members of the Practice Learning Team being dependent on the local needs of the clinical learning environment.…”
Section: The Negotiated Role Performed By the Nurse Lecturermentioning
confidence: 99%
“…In the past decade, several investigators [813] reported positive findings of collaborative preceptor models between schools of nursing and service agencies. Results of these studies showed that nursing students had a positive experience, expanded their knowledge, increased their confidence, and integrated their skills with real-life situations.…”
Section: Review Of the Literaturementioning
confidence: 99%